Providing affordable various types of passenger transport for disabled - K. E. Safronov; S. M. Mochalin (Вестник СибАДИ)
The quality of passenger transport services urban transport is made up of several indicators - the cost, speed, safety, comfort, reliability, cleanliness, service culture, information technology, environmental friendliness. All the more important given the recent availability of public transport for disabled people and people with limited mobility. The article is devoted to the method of ensuring the availability of different types of passenger transport, which includes the choice of forms of transport services and rolling stock.